Pengaruh Return on Aset, Current Ratio, Inflasi, Suku Bunga dan Capital expenditure terhadap Return Saham pada perusahaan sub sektor pertambangan Minyak dan Gas yang terdaftar di Bursa Efek Indonesia periode 2018-2022 - Ahmad Alamsyah; Andry Priharta (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to examine and analyze the influence of return on assets, current ratio, inflation, interest rates and capital expenditure on stock returns. This research method was carried out using an associative quantitative approach. The analytical tool used is panel data regression analysis with the help of Eviews version 12 software. The population in this research is all Oil and Gas companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The research results concluded that return on assets and current ratio had a significant effect on stock returns, while inflation, interest rates and capital expenditure had no significant effect on stock returns.